The association between parental marijuana use and mother-child interactions - Barmore, Bryer, author; Lunkenheimer, Erika, advisor; Riggs, Nathan, committee member; Conner, Bradley, committee member (Colorado State University. Libraries, 2016)
Little is known about parents who use marijuana even though it is the most commonly used illicit substance in the world (Cooper & Haney, 2014). Previous research has shown negative outcomes for children of parents who use illicit substances (Kelley, Lawrence, Milletich, Hollis, & Henson, 2015; Riggs, Chou, & Pentz, 2009). Regular marijuana use has been linked to overall poorer mental health, and parents with poor mental health has been linked to maladaptive outcomes for their children later in life (Arseneault et al., 2002; Van Loon et al., 2014). Dynamic systems theory was used to quantify mother-child dyadic interaction patterns, with a specific focus on adaptive flexibility, negativity, and rigidity. Higher levels of flexibility has been shown to moderate the transmission of risk from parent to child (Granic & Lamey, 2002). This was a longitudinal study at two time points using a non-randomized community sample and focused on associational differences in mother-child dyads based on lifetime frequency of parental marijuana use. Mothers who had a higher frequency of marijuana use had reduced levels of dyadic adaptive flexibility, even after controlling for maternal depressive symptoms and mother's race. When fathers had a higher frequency of marijuana use, mother-child dyads had increased rigidity, however, after controlling for maternal depressive symptoms and mother's race, the association became insignificant.